FISIOTERAPIA NEUROLÓGICA: ESTUDO DA PERCEPÇÃO VISUAL DE CORES EM CRIANÇAS DE 4 E 5 ANOS - Maçalai, Tuani R.; Delacoste, Fernanda B. C.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo